Nanostructured P-doped activated carbon with improved mesoporous texture derived from biomass for enhanced adsorption of industrial cationic dye contaminants - Khalil, Kamal M.S.; Elhamdy, Walaa A.; Mohammed, Khaled M.H.; Said, Abd El-Aziz A. (Materials chemistry and physics, 2022)
Developing of high-performance carbonaceous materials from biomass is a significant contemporary research subject to meet the increasing demand for functional adsorbents with low price, high available and sustainability for adsorptive removal processes of industrial pollutants. The present work investigates formation of nanostructured surface modified P-doped activated carbon (ACP) materials via thermochemical activation of orange peel (OP) biomass residual materials, by phosphoric acid, H3PO4. Different impregnation ratios of phosphoric acid to OP (w/w) were investigated at different activation temperatures (400–800 °C). The formed ACP materials were characterized by TGA−DTA, FTIR−ATR, Raman spectroscopy, XRD, N2 gas adsorption/desorption, HR−TEM microscopy, EDX and elemental surface mapping. The results indicated that ACP materials were structured in the form of plate-like nanoparticles of amorphous graphite that composed of few graphene layers. The ACP materials exhibited high surface area (up to 1700 m2/g) with high contribution from mesoporosity (up to 94%) of slit-like pore shape. The point of zero charge was found at pH of 6.3, which permits application at neutral adsorption conditions. The formed ACP adsorbents exhibited distinguished adsorption capacities, qads, for methylene blue (MB) with successful recyclability. The adsorption capacities were enhanced (up to qads = 452 mg/g) for the materials formed at high acid impregnation ration and activated at high temperatures. The adsorption process of MB was spontaneous, fits with the Langmuir adsorption isotherm and pseudo-second-order kinetic. The high adsorption capacities for the ACP adsorbents were correlated with their micro/nano-structures, which were dominated by nano plate−like amorphous graphite particles composed of few graphene−like layers. [Display omitted] •P-doped activated carbon ACP adsorbents were derived from orange peel residues.•ACPs were nanostructured into amorphous graphite nanoparticles of few graphene layers.•ACP adsorbents showed high surface up to 1700 m2/g with improved mesoporosity >90%.•ACPs showed remarkable adsorption capacity (452 mg/g) for methylene blue (MB) dye.